Tinjauan Teologi Moral Keutamaan Atas Kejahatan Padre Amaro (dalam Film The Crime of Padre Amaro) - Zakeus Daeng Lio (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2020)
This paper elaborates the Writer’s views on the crime committed by a Roman Catholic Priest as showed in the film entitled The Crime of Padre Amaro. The crime proceeded from the Priest’s closeness to a girl named Amelia, one of his Church members, advanced to mutual love and affection between them, accompanied with sexual relation as a husband and wife, until Amelia got pregnant, and was forced by Padre Amaro to have an abortion, which ended with Amelia’s death because of the abortion. The views on the crime are posed by the Writer from the perspectives of Principal Moral Theology, by elaborating some principal moral value judgements on Padre Amaro’s treatments towards Amelia. For the purpose the Writer is doing his best to show all the principal moral value aspects violated by Padre Amaro in the entire range of his unfavourable deeds. An explanation of the Holy Church views of Padre Amaro’s deeds are also briefly provided by the Writer. Drawing lesson learned from the violation and crime conducted by Padre Amaro, the Writer suggests some recommended measures that should be taken so that we will not fall into the same faults. Amongst them are Cultivating Conscience, Understanding and Considering Values in all our actions, and Holistic Sexuality Education.